Tropical Soil Labile Fractions of Copper in the Experimental Plots ±Ten Years after Application of Copper-Containing-Waste - Salam, Abdul Kadir; Ginanjar, Kiat (JOURNAL OF TROPICAL SOILS, 2018)
Copper is reported to be retained in soils for a quite long time particularly in soil treated with some amendments.  This research was intended to evaluate the soil labile fractions of Cu ±10 years after application of Cu-containing industrial waste, lime, and cassava-leaf compost.  Soil samples were taken from topsoils and subsoils of ±10 years old experimental plots set up in 1998 and factorially treated with a metal-spoon industrial waste at 0, 15, and 60 Mg ha-1, lime at 0 and 5 Mg ha-1, and cassava-leaf compost at 0 and 5 Mg ha-1.  The measured Cu labile fractions were compared to those in soils sampled at ±1.5 years and ±3 years after treatments. The results showed that the soil Cu labile fractions in waste treated soils were higher than those in the control treatments eventhough their concentrations decreased with the years of sampling.  Lime showed a decreasing effect on soil labile Cu fractions, but the effect decreased with the years of sampling. The effect of cassava-leaf compost application on soil Cu labile fraction was in general not evidenced ±10 years after treatment.